Quick Response Code Indonesian Standard System on the Mobile Banking Application of Mandiri Sharia Bank - Asra Febriani; Nedy Iswandi; Suci Annisa Tiara (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2021)
The Quick Response Code Indonesian standard  is one part of the digital-based payment instrument issued by Bank Indonesia which was adopted by Bank Syariah Mandiri  to facilitate customers in transacting. Currently all applications that have a QR code are required to use QRIS as a national standard. This study raises the issue of concepts, systems and mechanisms as well as the views of Islamic law regarding QRIS. The research method used  a field research with qualitative method with observations, interviews and documentation techniques. The results showed that QRIS is a halal product that has gone through the supervision process of the Dewan Pengawas Syari’ah  and has a DSN fatwa as the legality law for Bank Syariah Mandiri. QRIS mechanism by scanning the code available in the BSM Mobile Banking application. In addition to having practical and efficient benefits, QRIS is very safe so that customers are protected from criminal practices such as skimming and other types of theft. In addition, by using QRIS, customers can break the chain of the spread of Covid 19 because they do not make physical contact. The results of this study are very important for customers who use Bank Syariah Mandiri products so that they know that QRIS is a halal product, safe from all cyber crimes, flexible and reduces physical interaction in the pandemic era.